Potentiation of Thromboxane A2-induced Platelet Secretion by Gi Signaling through the Phosphoinositide-3 Kinase Pathway - Dangelmaier, Carol; Jin, Jianguo; Smith, Bryan J.; Kunapuli, Satya P. (Thrombosis and Haemostasis, 2001)
Platelet activation results in shape change, aggregation, generation of thromboxane A2, and release of granule contents. We have recently demonstrated that secreted ADP is essential for thromboxane A2-induced platelet aggregation (J. Biol. Chem. 274: 29108-29114, 1999). The aim of this study was to investigate the role of secreted ADP interacting at P2 receptor subtypes in platelet secretion. Platelet secretion induced by the thromboxane A2 mimetic U46619 was unaffected by adenosine-3’phosphate-5’-phosphate, a P2Y1 receptor selective antagonist. However, AR-C66096, a selective antagonist of the P2TAC receptor, inhibited U46619-induced platelet secretion, indicating an important role for Gi signaling in platelet secretion. Selective activation of either the P2TAC receptor or the α2A adrenergic receptor did not cause platelet secretion, but potentiated U46619-induced platelet secretion. SC57101, a fibrinogen receptor antagonist, failed to inhibit platelet secretion, demonstrating that outside-in signaling was not required for platelet secretion. Since Gi signaling results in reduction of basal cAMP levels through inhibition of adenylyl cyclase, we investigated whether this is the signaling event that potentiates platelet secretion. SQ22536 or dideoxyadenosine, inhibitors of adenylyl cyclase, failed to potentiate U46619-induced primary platelet secretion, indicating that reduction in cAMP levels does not directly contribute to platelet secretion. Wortmannin, a selective inhibitor of PI-3 kinase, minimally inhibited U46619-induced platelet secretion when it was solely mediated by Gq, but dramatically ablated the potentiation of Gi signaling. We conclude that signaling through the P2TAC receptor by secreted ADP causes positive feedback on platelet secretion through a PI-3 kinase pathway.
Keywords: Platelet activation; ADP; P2T AC receptor; epinephrine